Embedding Evidence‐based Practice Education into a Post‐graduate Physiotherapy Program: Eight Years of pre‐Post Course Evaluations. (19th February 2016) - Perraton, L.; Machotka, Z.; Grimmer, K.; Gibbs, C.; Mahar, C.; Kennedy, K.
Abstract: Background and Purpose: Little has been published about the effectiveness of training postgraduate physiotherapy coursework students in research methods and evidence‐based practice (EBP) theory. Graduate qualities in most universities include lifelong learning. Inclusion of EBP in post‐graduate coursework students' training is one way for students to develop the knowledge and skills needed to implement current best evidence in their clinical practice after graduation, thereby facilitating lifelong learning. This paper reports on change in confidence and anxiety in knowledge of statistical terminology and concepts related to research design and EBP in eight consecutive years of post‐graduate physiotherapy students at one Australian university. Methods: Pre‐survey/post‐survey instruments were administered to students in an intensive 3‐week post‐graduate course, which taught health research methods, biostatistics and EBP. This course was embedded into a post‐graduate physiotherapy programme from 2007 to 2014. The organization and delivery of the course was based on best pedagogical evidence for effectively teaching adult physiotherapists. The course was first delivered each year in the programme, and no other course was delivered concurrently. Results: There were significant improvements in confidence, significantly decreased anxiety and improvements in knowledge of statistical terminology and concepts related to research design and EBP, at course completion. Age, gender and country of origin were not confounders on learning outcomes, although there was a (non‐significant) trend that years of practice negatively impacted on learning outcomes ( p = 0.09). There was a greater improvement in confidence in statistical terminology than in concepts related to research design and EBP. Conclusion: An intensive teaching programme in health research methods and biostatistics and EBP, based on best practice adult physiotherapy learning principles, is effective immediately post‐course, in decreasing anxiety and increasing confidence in the terminology used in research methods and EBP. Copyright © 2016 John Wiley & Sons, Ltd.